Missing in action? The role of the knowledge mobilisation literature in developing knowledge mobilisation practices. (19th May 2017) - Powell, Alison; Davies, Huw; Nutley, Sandra
Abstract : Despite a burgeoning literature and the development of new theories about knowledge mobilisation in the past 15 years, findings from this online survey in 2014 of over 100 research agencies (n=106; response rate 57%) show the challenges of making effective use of formal and informal learning. Many agencies rely on traditional knowledge 'push' activities; formal use of theoretical models and frameworks is patchy; and knowledge-sharing between agencies and the comprehensive evaluation of knowledge mobilisation programmes are limited. Closer links between research agencies, and between these and knowledge mobilisation researchers, could enhance future knowledge mobilisation practice and theory.